Erratum to: Use of a MAIT Activating Ligand, 5-OP-RU, as a Mucosal Adjuvant in a Murine Model of Vibrio cholerae O1 Vaccination - Owen Jensen; Shubhanshi Trivedi; Jackson G. Cacioppo; Kelin Li; Jeffrey Aubé; J. Scott Hale; Edward T. Ryan; Daniel T Leung (Case Western Reserve University, 2022)
ERRATUM TO: USE OF A MAIT ACTIVATING LIGAND, 5-OP-RU, AS A MUCOSAL ADJUVANT IN A MURINE MODEL OF VIBRIO CHOLERAE O1 VACCINATION DOI: 10.20411/pai.v7i1.525 Reason: The authors sincerely regret the inadvertent omission of Jackson G. Cacioppo as coauthor of this work. He has no additional conflicts of interest.  Corrected version: Owen Jensen1,2, Shubhanshi Trivedi1, Jackson G. Cacioppo3, Kelin Li3, Jeffrey Aubé3, J. Scott Hale2, Edward T. Ryan4,5,6, Daniel T. Leung1, 2*